Navigating disruption in the PID landscape: embracing opportunities and anticipating threats in the next ten years - Mamede, Lúcia; Sabà, Roser Cantenys; Van Coillie, Samya; Prévot, Johan; Sánchez-Ramón, Silvia; Poli, Cecilia; Barasa, Anne; Schuller, Björn W.; Hendel, Ayal; Garcelon, Nicolas; Boersma, Cornelis; Lee, Pamela; et al. (Frontiers in Immunology, 2025)
IntroductionThe International Patient Organisation for Primary Immunodeficiencies (IPOPI) held its third edition of the Global Multi-Stakeholders’ Summit, gathering key primary immunodeficiencies (PID) stakeholders and experts to discuss and foment global collaboration.MethodsThis edition focused on the impact of genomic medicine in PID treatment, the role of digital health, including artificial intelligence, in PID care, and how to anticipate and minimise risks to ensure optimal patient access to care.ResultsThese discussions aimed to examine current hurdles and brainstorm feasible solutions and priorities for the PID community in these areas in the next ten years.DiscussionThese discussions led to recommendations for comprehensive approaches to care and access to treatment for PID patients, suggesting actions that will bring the community closer to treatments based on real-world evidence and adjusted to patient’s needs. To accomplish this, collaboration between academia, industry, regulatory authorities, and patients is crucial.